(untitled) (Journal of Science and Technology, 2016)
Microemulsions are thermodynamically stable, clear, transparent fluid dispersions of oil, water, and surfactant, but may include a cosurfactant typically a short chain alcohol. The unique properties of microemulsions make them suitable candidates as vehicles for improving parenteral drug delivery. In the present study, we report of our investigations into the ability of some commercial non-ionic surfactants to produce o/w microemulsions with different oils and water or phosphate buffered saline (PBS), their physicochemical properties and modulation of haemolytic activity on human erythrocytes. The compositions over which clear o/w microemulsion systems formed and their areas of existence were dependent on the structure of the non-ionic surfactant and the oil incorporated. The clear o/w microemulsion systems remained clear and stable even on dilution with water or PBS. The haemolytic activities of the micellar solutions of the non-ionic surfactants were dependent on the nature and concentration of the surfactant. Generally, the clear o/w microemulsion systems were greatly less haemolytic than their corresponding micellar solutions at equivalent concentrations of surfactant. This indicated a high modulation of the haemolytic activity of the surfactants by the microemulsion formulations. The modulation of haemolytic activity was greatest with microemulsions formulated with the highest possible oil/surfactant ratios. The use of relatively longer triglycerides (oils) greatly enhanced the modulation activity of the resultant microemulsions. Our findings signified a high level of safety associated with the o/w microemulsions and lent a good support and credence to the high potential of microemulsions as suitable and safe vehicles for parenteral drug administration.